Rainfall Variability, Occupational Choice, and Welfare in Rural Bangladesh - Bandyopadhyay, Sushenjit (World Bank, Washington, DC, 2012)
This study investigates the choice of occupational focus versus diversification between household members in rural Bangladesh as an autonomous and proactive adaptation strategy against ex ante local rainfall variability risks. The analysis combines nationally representative household level survey data with historical climate variability information at the Upazila level. The authors note that flood prone Upazilas may face reduced risks from local rainfall variability as compared with non-flood prone Upazilas. They find that two members of the same household are less likely to be self-employed in agriculture if they live in an area with high local rainfall variability. However, the occupational diversification strategy comes at a cost to households in terms of consumption welfare. The paper considers the effects of three policy actions, providing access to credit, safety net, and market. Access to market appears to be more effective in reducing the likelihood of costly within-household occupational diversification as an ex ante climate risk-reducing strategy as compared with access to credit and safety net.